Tagging Freedom - Roumani, Rhonda (New York : Union Square Kids, 2023)
Set in the early days of the Syrian Civil War, cousins Kareem and Samira living in Massachusetts navigate the growing conflict in Syria, new friendships, and the use of art to express themselves.
new kids book 2025 winter.
Ages 8-12.
Keywords: Graffiti -- Fiction; Syrian Americans -- Fiction; Syrians -- Massachusetts -- Fiction; Syria -- History -- Civil War, 2011- -- Fiction; JUVENILE FICTION / People & Places / United States / Middle Eastern & Arab American; JUVENILE FICTION / Art; Cousins -- Fiction